2023
DOI: 10.3389/fonc.2022.1043199
|View full text |Cite
|
Sign up to set email alerts
|

Treatment dependent impact of plasma-derived exosomes from head and neck cancer patients on the epithelial-to-mesenchymal transition

Abstract: BackgroundEpithelial to mesenchymal transition (EMT) is a key process in carcinogenesis of head and neck squamous cell carcinoma (HNSCC), contributing to tumor invasiveness, distant metastasis, and recurrence. Exosomes are known mediators and regulators of EMT. Here, we analyze the impact of exosomes that were primed by conventional therapy on EMT modulation.MethodsPlasmas of n = 22 HNSCC patients were collected before and after standard of care surgery and adjuvant or primary (chemo)radiotherapy. Exosomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Additional studies are essential, but identifying the changes in plasma TDEV proteomes, transcriptomes, and metabolomes before, during, and after therapy may accurately reflect cellular evolution in the primary TIME. These observations have significant translational implications for monitoring treatment response and disease recurrence 85 . Future applications of this approach have the potential to transform the care of patients with HPV + OPSCC.…”
Section: Exosomes and Tumor-derived Extracellular Vesiclesmentioning
confidence: 97%
See 3 more Smart Citations
“…Additional studies are essential, but identifying the changes in plasma TDEV proteomes, transcriptomes, and metabolomes before, during, and after therapy may accurately reflect cellular evolution in the primary TIME. These observations have significant translational implications for monitoring treatment response and disease recurrence 85 . Future applications of this approach have the potential to transform the care of patients with HPV + OPSCC.…”
Section: Exosomes and Tumor-derived Extracellular Vesiclesmentioning
confidence: 97%
“…Emerging insights into the mechanisms underlying TDEV reprogramming of the TIME will provide new opportunities to study selective TDEV-depleting strategies and interventional approaches in the clinical realm. A recent study evaluating whether conventional therapies influenced plasma TDEV cargo and function found that the cargo of TDEVs and their ability to induce an epithelial-to-mesenchymal transition was significantly enhanced after treatment 85,86 . Because the cargo carried by EVs has been involved in the modulation of tumor phenotypic transitions and progression, an exciting approach for the future is the possibility of targeting specific TDEV cargos with oncogenic properties to prevent progression and metastasis.…”
Section: Exosomes and Tumor-derived Extracellular Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hofmann et al. haben kürzlich in einem Kollektiv von 22 Patienten gezeigt, dass Operationen und/oder Radiochemotherapie unterschiedliche Veränderungen der Tumorexosomen bedingen [ 7 ]. Die Induktion von epithelialer zu mesenchymaler Differenzierung bei Applikation von Tumorexosomen an Zellen ist ein mögliches Maß für das Tumoransprechen.…”
Section: Definition Von „Liquid Biopsy“unclassified